Apakah Infrastruktur Penting terhadap Kunjungan Wisatawan ke Indonesia dan Negara-Negara Asean? - Anak Agung Bagus Putu Widanta; Anak Agung Ketut Ayuningsasi; Ida Bagus Putu Purbadharmaja; Dewa Jati Primajana (CV. Creative Tugu Pena, 2026)
Tourist arrivals and tourism revenue remain key indicators of economic performance in the tourism sector. In 2018, countries in the ASEAN region collectively attracted approximately 129.2 million international visitors. Indonesia received around 15.8 million foreign tourists in the same year. Despite its substantial tourism potential—supported by rich natural resources, cultural diversity, and abundant human capital—Indonesia ranked fourth in tourist arrivals, behind Thailand, Malaysia, and Singapore, and only slightly above Vietnam. This suggests that tourism potential alone is not the primary determinant of tourist visits in Southeast Asia. Instead, the availability of adequate infrastructure plays a more significant role in supporting tourism demand. Improvements in infrastructure generally enhance population mobility and increase tourist arrivals by providing better accessibility and safety for visitors.Amid global market changes and intensifying international tourism competition, effective strategies are required to maintain tourism attractiveness and position destinations as primary choices for travelers. This study employs multiple linear regression analysis to examine the influence of infrastructure sub-indicators—air transport, land transport, and tourism service facilities—on tourist arrivals in Indonesia and several other ASEAN countries. The findings are expected to provide insights into the impact of infrastructure development on tourism performance across the region. Furthermore, the results aim to assist policymakers and stakeholders in prioritizing infrastructure projects that support tourism growth, increase visitor numbers, and contribute to overall economic development.